La satisfacción laboral y su relación en el desempeño de los trabajadores del Sindicato Provincial Choferes de Loja - Torres Ureña, Stephanie (2023)
Job satisfaction is the general attitude that people have towards their work. This attitude is based on the beliefs and values of each individual. Job satisfaction goes hand in hand with job performance which represents the efficiency that an employee shows when completing a job, which is required by the company. The objective of this research was to establish the relationship between job satisfaction and job performance of the administrative staff of the Loja provincial drivers' union, and based on this relationship, to make a proposal to improve both aspects through a plan of activities. The methodology was framed in a mixed approach with a descriptive-correlational scope. A non-probabilistic purposive sampling was applied and a survey was used as a data collection technique applied to 90 employees to determine the level of job satisfaction and performance. All data analysis was performed in SPSS v. 29.0.0.0. The main findings showed that job satisfaction and performance presented a positive relationship where most of the workers of the organization are satisfied with the work environment offered by the institution, however, others are dissatisfied with the compensation plans and the lack of opportunities for professional growth. It is concluded that through the plan of activities, the administrative staff is professionally motivated to achieve the institutional goals and objectives, maintaining a favorable work environment for the proper performance and progress of the provincial union of drivers of Loja.